Antibiotics and adverse events: the role of antimicrobial stewardship programs in 'doing no harm'. Issue 6 (December 2019) - Bauer, Karri A.; Kullar, Ravina; Gilchrist, Mark; File, Thomas M.
Abstract : Purpose of review: Antimicrobial resistance (AMR) is a global threat worldwide, with deaths associated with AMR infections projected to exceed 10 million per year by the year 2050. The overuse and misuse of antibiotics is the primary driver of this resistance, with up to 50% of antibiotics prescribed in the hospital setting being either unnecessary or inappropriate. Antimicrobial stewardship (AMS) programs (ASPs) can mitigate some of this resistance, with the benefits well recognized; however, if we are to truly advance the state of AMS, the principles and practices should align with patient safety. Recent findings: In a recent evaluation, among 1488 adult patients receiving systemic antibiotic therapy, 298 (20%) experienced at least one antibiotic-associated adverse drug event (ADE). Fifty-six (20%) nonclinically indicated antibiotic regimens were associated with an ADE. It is also well recognized that besides ADEs, the inappropriate use of antibiotics is associated the development of multidrug-resistant infections and Clostridium difficile infection. Summary: Currently, there is a significant gap in ASPs correlating initiatives with patient safety goals, including reductions in antibiotic-associated ADEs and multidrug-resistant infections. Therefore, in this article, we provide the rationale for why ASPs are best suited to lead a collaborative effort to prevent antibiotic-associated ADEs and multidrug-resistant infections.